Review of Clinical Trials of COVID-19 Vaccination Booster in SARS-CoV-2 Variants Era: To Take It or Not To Take It - Yan, Michael Zhipeng; Yang, Ming; Lai, Ching-Lung (Frontiers in Drug Discovery, 2022)
Since the COVID-19 outbreak in China in 2019, the pandemic has spread globally. There is no definitive cure, but vaccines have greatly protected humans from symptomatic infections and severe complications. However, vaccine efficacy has been greatly reduced by the advent of SARS-CoV-2 variants worldwide. The World Health Organization has classified the variants into two groups: variants of concern (Alpha, Beta, Gamma, Delta, Omicron) and variants of interest (Lambda, Mu). Clinical trials and modifications of vaccines are currently undertaken to improve their clinical efficacies. This is particularly worrying in immunocompromised patients since breakthrough infections with multiple lineages of variants can pose a continuous threat of severe diseases in these vulnerable subjects, though there is no evidence showing immunocompromised patients are at a higher risk of vaccine-associated adverse events. However, there is no consensus on the schedule, benefits, and risks as well as contraindications (both absolute and relative) of receiving booster vaccinations. This review looks into the efficacy and safety of COVID-19 vaccination booster to guide clinical decisions on when and who to receive booster vaccination.